Quantifying turnover in biodiversity of British breeding birds. Issue 2 (26th October 2015) - Harrison, Philip J.; Yuan, Yuan; Buckland, Stephen T.; Oedekoven, Cornelia S.; Elston, David A.; Brewer, Mark J.; Johnston, Alison; Pearce‐Higgins, James W.
Summary: A key aspect of monitoring regional changes in biodiversity is to quantify the temporal turnover in communities. Turnover has traditionally been assessed by observing range change. However, we are often interested in trends in biodiversity of large regions as opposed to single sites, as with Convention for Biological Diversity targets. Extinctions and colonizations tend to be rare events at the regional level; changes in species proportions estimated from spatio‐temporal models of species abundance are then more sensitive measures of community change. We investigated three measures for quantifying turnover based on species proportions, and estimated how each varies across Great Britain using data from the British Trust for Ornithology's Breeding Bird Survey. All three measures identify high turnover associated with loss of biodiversity in the south‐east of England. This seems to be driven by changes in the farmland bird community, and by turnover in the scarcer species of the woodland bird community. The measures also show evidence of high turnover in the west of Scotland; these changes may be linked to climate change, although precision in our measures for this region is relatively poor due to low survey effort. Policy implications . Turnover in ecological communities may be quantified by modelling species abundance, and measuring how resulting species proportions change over time. When used alongside estimated temporal trends in biodiversity, these can identify areas and communities showing greatest evidence for change. How, and indeed even whether, society should respond to such changes depends on further investigation into the causes of the changes, and the extent to which these are seen as undesirable and avoidable. For those communities with adequate survey data, we recommend that these methods augment the suite of measures used for routine assessment of change, hence acting as a more sensitive trigger to set in motion exploration of causes and consideration of adaptive actions to be taken by land managers and policymakers. Abstract : Turnover in ecological communities may be quantified by modelling species abundance, and measuring how resulting species proportions change over time. When used alongside estimated temporal trends in biodiversity, these can identify areas and communities showing greatest evidence for change. How, and indeed even whether, society should respond to such changes depends on further investigation into the causes of the changes, and the extent to which these are seen as undesirable and avoidable. For those communities with adequate survey data, we recommend that these methods augment the suite of measures used for routine assessment of change, hence acting as a more sensitive trigger to set in motion exploration of causes and consideration of adaptive actions to be taken by land managers and policymakers.